Force of the air pressure on a moving plate - Gretchikhin, Leonid I. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper developed a mathematical model of gas dynamic fluid flow for a flat plate during its movement with positive and negative angles of attack. It is shown that at low velocities, the lifting force and the frontal resistance are determined by gasdynamic air flow in the fluid flow exit area​​while at velocities close to the speed of sound the decisive role is played by a mutualeffect of the pplate coliding with molecules of the surrounding environment in the fluid flow incidence field. The airflow behind the plate does not appear at low velocities. The conditions when the frontal resistance and the lifting force change the sign are determined.